A nutrition/health mindset on commercial Big Data and drivers of food demand in modern and traditional systems. (16th December 2014) - Dubé, Laurette; Labban, Alice; Moubarac, Jean‐Claude; Heslop, Gabriela; Ma, Yu; Paquet, Catherine
Abstract : Building greater reciprocity between traditional and modern food systems and better convergence of human and economic development outcomes may enable the production and consumption of accessible, affordable, and appealing nutritious food for all. Information being key to such transformations, this roadmap paper offers a strategy that capitalizes on Big Data and advanced analytics, setting the foundation for an integrative intersectoral knowledge platform to better inform and monitor behavioral change and ecosystem transformation. Building upon the four P's of marketing (product, price, promotion, placement), we examine digital commercial marketing data through the lenses of the four A's of food security (availability, accessibility, affordability, appeal) using advanced consumer choice analytics for archetypal traditional (fresh fruits and vegetables) and modern (soft drinks) product categories. We demonstrate that business practices typically associated with the latter also have an important, if not more important, impact on purchases of the former category. Implications and limitations of the approach are discussed.